PENGARUH MODEL PEMBELAJARAN QUANTUM LEARNING BERNUANSA MUSIK KLASIK TERHADAP HASIL BELAJAR IPA KELAS VI SD DI PEKANBARU - Panji Husairi; Neni Hermita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is motivated by the not yet optimal learning outcomes of sixth grade science in Pekanbaru Elementary School, through the results of direct interviews with several elementary school students in sixth grade, it is known that most students find it easier to learn while listening to audio rather than visual and kinesthetic. This study aims to find out: (1) the influence of quantum learning model nuances of Mozart's music on learning outcomes of class VIb Science at SD Negeri 82 Pekanbaru; and (2) the influence of the quantum learning model with Beathoven music nuances on learning outcomes of science class VI in SD Negeri 58 Pekanbaru. This research is an experimental research with true-experimental design, namely posttest only control design. The results showed that: (1) there was the influence of quantum learning model nuances of Mozart's music on learning outcomes of class VIb Science in SD Negeri 82 Pekanbaru. It is known from the value of the tcount> value t table (3.037> 2.064). Thus, the research hypothesis which is said is thought to have the influence of quantum learning model nuances of Mozart's music on learning outcomes of science class VIb SD Negeri 82 Pekanbaru, accepted; and (2) there is the influence of the quantum learning model nuanced by Beathoven music on learning outcomes of the sixth grade science of Pekanbaru Pekanbaru Elementary School. It is known from the value of tcount> ttable (2.834> 2.093). However, after comparing the two learning outcomes of the experimental group, it was found that there was no difference, because tcount <value t table (0.509 <2.014). Thus, the research hypothesis which is said to be presumed to have the influence of the quantum learning model nuances of Beathoven music on the learning outcomes of class VIa Science in Pekanbaru Elementary School 58, was accepted.